Initial result on low cost microprocessor and ethernet controller based data acquisition system for optical tomography system - Hj. Abdul Rahim, Ruzairi; Goh, Chiew Loon; Rahiman, Mohd. Hafiz Fazalul; Chan, Kok San; Pang, Jon Fea; Leong, Lai Chan (International Frequency Sensors Association (IFSA), 2007)
Due to high cost of data acquisition card in the market, this research concentrates on developing a high speed, low cost microprocessor and Ethernet controller based data acquisition for optical tomography system. Microprocessor is the main core to control the sensor circuitry while the Ethernet controller has the responsibility of transmitting data to PC and thus insuring the reliability of data. The data transfer rate will be up to Megabit per second (Mbps). In this optical tomography system, a projection geometry combining two orthogonal and two rectilinear in one layer is modeled.